Positive and negative aspects of the COVID-19 pandemic among a diverse sample of US adults: an exploratory mixed-methods analysis of online survey data - Stephanie A Ponce; Alexis Green; Paula D. Strassle; Anna María Nápoles (BMC, 2024)
Abstract Background The COVID-19 pandemic had a profound social and economic impact across the United States due to the lockdowns and consequent changes to everyday activities in social spaces. Methods The COVID-19's Unequal Racial Burden (CURB) survey was a nationally representative, online survey of 5,500 American Indian/Alaska Native, Asian, Black/African American, Latino (English- and Spanish-speaking), Native Hawaiian/Pacific Islander, White, and multiracial adults living in the U.S. For this analysis, we used data from the 1,931 participants who responded to the 6-month follow-up survey conducted between 8/16/2021-9/9/2021. As part of the follow-up survey, participants were asked "What was the worst thing about the pandemic that you experienced?" and "Was there anything positive in your life that resulted from the pandemic?" Verbatim responses were coded independently by two coders using open and axial coding techniques to identify salient themes, definitions of themes, and illustrative quotes, with reconciliation across coders. Chi-square tests were used to estimate the association between sociodemographics and salient themes. Results Commonly reported negative themes among participants reflected disrupted lifestyle/routine (27.4%), not seeing family and friends (9.8%), and negative economic impacts (10.0%). Positive themes included improved relationships (16.9%), improved financial situation (10.1%), and positive employment changes (9.8%). Differences in themes were seen across race-ethnicity, gender, and age; for example, adults ≥ 65 years old, compared to adults 18-64, were more likely to report disrupted routine/lifestyle (37.6% vs. 24.2%, p < 0.001) as a negative aspect of the pandemic, and Spanish-speaking Latino adults were much more likely to report improved relationships compared to other racial-ethnic groups (31.1% vs. 14.8-18.6%, p = 0.03). Discussion Positive and negative experiences during the COVID-19 pandemic varied widely and differed across race-ethnicity, gender, and age. Future public health interventions should work to mitigate negative social and economic impacts and facilitate posttraumatic growth associated with pandemics.